PENATALAKSANAAN FISIOTERAPI PADA KONDISI POST OPERASI FRAKTUR SUPRACONDYLER HUMERI SINISTRA DENGAN PEMASANGAN NAIL AND WIRE - Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2011)
Many found case of Fractur supracondyler humeri sinistra which caused by accident and its elbow used for the antiers to heavy the body. This condition will generate the problems of physical capacities in the form of pain in bone, spasme of muscle and limitation of LGS. As for functional ability problems difficulty of moment for activity toileting, treatment of everyday activity and x'self entangling arm of fraktur. Research method used by case study. After get the treatment in therapy during 6x therapy ( T1-T6) with the Infra Red, Massage, Therapy of Practice and TENS getting a well enough result. As for its therapy is degradation assess the pain in bone kept quiet from value 2 becoming value 1, pain in bone depress from value 4 becoming value 2 and pain in bone move from value 6 becoming value 5,spasme muscle decrease from value 2 becoming value 1, active improvement LGS area sagital from S = 50-00-900 becoming S = 50-00-1000 and area of giration R ( s900) = 800-00-750 becoming R ( s900) = 900-00-800, passive improvement LGS [at] area of sagital S = 50-00-1100 becoming S = 100-00-1200 area of giration R ( s900) = 850-00-850 becoming R ( s900) = 950-00-850. Make-Up of value ADL of dressy activity from value 2 becoming value 1, cleaning from value 3 becoming value 2, bath from value 2 becoming value 1, using toilet from value 2 becoming value 1, dressing smartly from value 2 becoming value 1 and prepare to drink from value 2 becoming value 1.Key Word : Fractur supracondyler humeri sinistra, Infra Red, Massage, aktif and pasif movement, Hold Relax dan TENS.